Exploring the potential role of shopping malls in community disaster response - Cacalda, Precious Anne L.; Ramos, Grace C. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
The occurrence of frequent extreme natural disasters is held to be the new normal. While the Local Government Units (LGUs) are currently integrating the disaster risk reduction and management plan on their programs, preparedness is way behind in terms of infrastructure. The local government cannot solely build a dedicated structure to shelter and accommodate residents seeking refuge; rather most of the time schools, barangay halls and churches instantly become a home to more than a hundred families in time of calamities. It is always being shown on media reports the condition of these places as inadequate to shelter nearly a thousand people. Another problem arises from relief distribution as a multitude of evacuees often overwhelms the local government units. While these facilities serve the purpose in times of need. It is best to look at potential of shopping malls will explored, just like schools and churches which have its own coverage of service or the trade area. Malls can be found everywhere and are readily accessible by public transport and strategically located in nodes and conceived in the context of its trade area, these structures can be used to create a network of shelters and relief distribution centers to accommodate its surrounding community in times of calamities.
includes appendices
Thesis (Master of Architecture) -- University of the Philippines Diliman
Keywords: Malls as evacuation area